Health disparities in pediatric sleep-disordered breathing. (March 2023) - Williamson, Ariel A.; Johnson, Tiffani J.; Tapia, Ignacio E.
Abstract: Sleep-disordered breathing reflects a continuum of overnight breathing difficulties, ranging from mild snoring to obstructive sleep apnea syndrome. Sleep-disordered breathing in childhood is associated with significant adverse outcomes in multiple domains of functioning. This review summarizes the evidence of well-described ethnic, racial, and socioeconomic disparities in pediatric sleep-disordered breathing, from its prevalence to its treatment-related outcomes. Research on potential socio-ecological contributors to these disparities is also reviewed. Critical future research directions include the development of interventions that address the modifiable social and environmental determinants of these health disparities.